Principios teatrales para docentes - Arroyo Zúñiga, R. Irene (2011)
This study intends to give teachers tools so that they can use them as part of the activities included in a lesson plan. An analysis of the elements that make up the art of the scenic representation is also included. 1. Body expression: It’s the capacity to express emotions using body movements only. 2. Vocal training: It’s the ability of projecting the voice without hurting the vocal cords. 3. Diction: It’s the correct pronunciation of words. 4. Acting: It’s the ability of creating a character from expressive resources in a natural way taking into account the students’ natural reaction. Improvisation technique: In this article, the author offers six steps that can be useful when using the theater as a didactic resource. Throughout history, the theater has been used to transmit knowledge, values, beliefs and all kinds of aspects inherent to the individual and his/ her environment. Thus, teachers must take advantage of what the theater offers.